Comparison of Laparoscopic Total Extra Peritoneal (TEP)Techniques versus Transabdominal Preperitoneal (TAPP) Technique for Inguinal Hernia Repair - Tariq Nawaz,Muhammad Waqas Ayub,Faisal Murad,Qasim Ali,Atif Khan,Idrees Anwar, (Journal of Rawalpindi Medical College, 2015)
Background: To Compare laparoscopic total extra peritoneal (TEP)techniques with transabdominal preperitoneal (TAPP) technique for inguinal hernia repair Methods: In this randomized controlled trial 120 patients undergoing herniorraphy were divided into two groups .Sixty patients into Laparoscopic Total Extra Peritoneal (TEP)Techniques group and 60 into Transabdominal Preperitoneal (TAPP) Technique group. TAPP required access to the peritoneal cavity with placement of a mesh through a peritoneal incision. Mesh was placed in the preperitoneal space covering all potential hernias sites in the inguinal region leaving it between the preperitoneal tissues and the abdominal wall where it becomes incorporated by fibrous tissue. In TAPP pneumo-peritoneum was created by open technique, circular incision was given on peritoneum. Peritoneum was lifted, proline light weight mesh was placed, and peritoneum was stitched with continued suture. In TEP, the peritoneal cavity was not entered, infra-umbilical trocar was inserted in the preperitoneal space, space was created with camera, and mesh was used to seal the hernia from outside the peritoneum. Both techniques were compared in terms of mean operative time, conversion to open procedure, post operative pain, length of hospital stay, port site infection, mesh infection, return to daily activity, deep infection and recurrence.All patients were followed for a period of 1 year Results: Mean operative time in TEP repair was 45.1 ± 3.54 minutes, whereas in TAPP repair was 70 ± 6.01 minutes (p=0.000). Five laparoscopic TEP were converted to open repair due to major breach in peritoneum. In TEP group 40 patients complained mild pain. In TAPP group 25 patients complained mild pain and 30 complained moderate pain(p= 0.015). Average requirement of analgesia in TEP group was 2 doses of I/M dicloran whereas average requirement of analgesia in TAPP group was 3 doses. Length of hospital stay in both groups was one day. In TEP group no patient developed port site infection whereas 1 patient in TAPP group developed port site infection. One patient developed mesh infection in each group. In TEP group return to daily activity was 4 days where as in TAPP group return to daily activity was 5 days. No patient developed deep site infection in both groups. There was no recurrence in one year follow up. Conclusion: TEP has advantage of short operative time and less post operative pain and therefore less requirement of analgesia and early return to daily activity, where as TAPP is superior, there being less chance of conversion